Analisis Indikator Ecoliteracy Perspektif Goleman Pada Buku Siswa Kelas IV Tema 9 Kayanya Negeriku - Siti Nurhalisa; Dyah Lyesmaya; Iis Nurasiah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
The purpose of this study was to describe the suitability of the ecoliteracy content contained in the fourth grade students' book theme 9 riches of my country with the Goleman perspective ecoliteracy indicator which is focused on social studies subject matter. The indicators are 1) developing empathy for all forms of life, 2) practicing survival as the action of community groups, 3) making things that are invisible become visible, 4) anticipating unexpected impacts, and 5) understanding how natural life takes place. This type of research used in this study is a qualitative descriptive method. The method of collecting data in this study used content analysis. Content analysis aims to describe the characteristics of the content or messages objectively, where the results of the analysis will be generally presented and then concluded. The results showed that there were five indicators of Goleman's perspective ecoliteracy found in student books from sub-themes 1 to 3 in 26 sentences of social studies material.